Evil by Design : Interaction design to lead us into temptation. - Nodder, Chris (Wiley, 2013)
How to make customers feel good about doing what you want Learn how companies make us feel good about doing what they want. Approaching persuasive design from the dark side, this book melds psychology, marketing, and design concepts to show why we're susceptible to certain persuasive techniques. Packed with examples from every nook and cranny of the web, it provides easily digestible and applicable patterns for putting these design techniques to work. Organized by the seven deadly sins, it includes: Pride - use social proof to position your product in line with your visitor.